Ex-ante and ex-post effects of price limits in commodity futures markets - Blair Fontinelle, Gabriel (Kansas State University, 2020)
After October 1987, financial crisis, market regulators created dispositive called circuit breaks to contain high levels of volatility. As a type of circuit breaker, price limits were adopted not only on stock markets but in commodity futures contracts as well, however, its effects are not clear. The present study aimed to evaluate price limit ex-ante effects on the four major wheat futures markets by adopting Brogaard and Roshak (2015) methodology by estimating the probability of extreme movements and limit moves conditional to extreme movements and its ex-post effects on trading activity by contrasting the volume curve on limit days with a counterfactual volume curve that simulates a scenario where price limits were not hit. The results show that tighter limit levels decrease the probability of extreme movements by approximately 0.008% having an overall (four markets included) baseline probability of extreme moves equals 1.11% which agrees with the Holding Back hypothesis assuming extreme movements as a proxy for volatility. On the other hand, the probability of limit moves conditional to extreme movements increases when limit levels are tighter by approximately 0.066% with an overall baseline of 0.05% which supports the “Magnet” hypothesis. Regarding the ex-post effects, longer periods where prices stay at the limit level result in trading activity lost, however, if prices return to limit range but bounce back to a limit lock, the longer the gap between limit locks trading session experience an increase in trading activity. Moreover, the ex-post effects on trading activity are more intense in Chicago relative to Kansas City because Chicago presents a higher trading volume on average.
Keywords: Price Limits